65.1k views
3 votes
Match solutions and differential equations. Note: Each equation may have more than one solution. Select all that apply. (a) 7y'' − 7y = 0 y = ex y = x3 y = e−x y = x−2 (b) 7x2y'' + 14xy' − 14y = 0 y = ex y = x3 y = e−x y = x−2 (c) 7x2y'' − 42y = 0 y = ex y = x3 y = e−x

User Wolfrevo
by
4.8k points

2 Answers

3 votes

Answer:

a-
e^x,e^(-x)

b-
x^(-2)

c-
x^3

Explanation:

a.7 y''-7 y =0

Auxillary equation


D^2-1=0


(D-1)(D+1)=0

D=1,-1

Then , the solution of given differential equation


y=e^x,y=e^(-x)

2.
7x^2y''+14xy'-14 y=0

Y=
y=x^3


y=3x^2


y''=6x

Substitute in the given differential equation


42x^3+42x^3-14x^3\\eq 0

Hence,
x^3 is not a solution of given differential equation


e^x,e^(-x) are also not a solution of given differential equation.

y=
x^(-2)


y'=-2x^(-3)


y''=6x^(-4)

Substitute the values in the differential equation


7x^2(6x^(-4))+14x(-2x^(-3))-14 x^(-2)

=
42x^(-2)-28x^(-2)-14x^(-2)=0

Hence,
x^(-2) is a solution of given differential equation.

c.
7x^2y''-42y=0


y=x^3


y'=3x^2


y''=6x

Substitute the values in the differential equation


42x^3-42x^3=0

Hence,
x^3 is a solution of given differential equation.

a-
e^x,e^(-x)

b-
x^(-2)

c-
x^3

User Nicolas Boisvert
by
5.3k points
2 votes

Answer:

a)
\boxed{7y''-7y=0\to y=e^(-x)}.

b)
\boxed{7x^2y''+14xy'-14y=0\to y=x^(-2)}

c)
\boxed{7x^2y''-42y=0\to y=x^(-2)}


\boxed{7x^2y''-42y=0\to y=x^(3)}

Explanation:

a) The given differential equation is:
7y''-7y=0.

The characteristic equation is:
7m^2-7=0

This implies that:
m=-1\:or\:\:m=1

The auxiliary solution to this second order homogeneous differential equation is:
y=Ae^(m_1x)+Be^(m_2x)

Therefore any equation of the
y=Ae^(x)+Be^(-x) where A and B are constants is a solution
7y''-7y=0.


\boxed{7y''-7y=0\to y=e^x}.


\boxed{7y''-7y=0\to y=e^(-x)}.

b) The given differential equation is:
7x^2y''+14xy'-14y=0

The characteristic equation is given by:
am(m-1)+bm+c=0, where a=7, b=14 and c=-14

This implies that:


7m(m-1)+14m-14=0


\implies m=-2\:or\:1

The auxiliary equation is of the form:
y=Ax^(m_1)+Bx^(m_2) where A and B are constants.

Hence any equation of the form:
y=Ax^(-2)+Bx is a solution to


7x^2y''+14xy'-14y=0


\boxed{7x^2y''+14xy'-14y=0\to y=x^(-2)}

c) The given differential equation is:
7x^2y''-42y=0

The characteristic equation is given by:
am(m-1)+bm+c=0, where a=7, b=0 and c=-42

This implies that:


7m(m-1)-42=0


\implies m=-2\:or\:3

The auxiliary equation is of the form:
y=Ax^(m_1)+Bx^(m_2) where A and B are constants.

Hence any equation of the form:
y=Ax^(-2)+Bx^3 is a solution to


7x^2y''-42y=0


\boxed{7x^2y''-42y=0\to y=x^(-2)}


\boxed{7x^2y''-42y=0\to y=x^(3)}

User Anhquan
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.